Autoavaliação de curso: criação de uma plataforma de evidências e autoavaliação de cursos de graduação - Oliveira, Anderson Luiz de (Universidade Federal do Tocantins, 2021)
Self-assessment is a necessary process for the continuous improvement of the quality and effectiveness of any course and in any type of offer, in person or at a distance. Based on an exploratory research, we did not find tools or digital platforms that, in addition to enabling this self-assessment, were aligned with the Assessment Instrument for On-site or Distance Undergraduate Courses provided by the National Institute of Educational Studies and Research Anísio Teixeira of the Ministry of Education. The main objective of this work was to develop an online platform that would help in the self-assessment of undergraduate courses at Universidade Federal do Tocantins. The purpose of this environment, now, is not to generate grades, whether quantitative or qualitative, it first seeks to provide peers' self-knowledge about the course and about the assessment instrument itself. The Self-Assessment and Evidence Platform, entitled, Evidence+, comes to assist in the self-assessment of undergraduate courses, also enabling to add evidence of course actions or practices that collaborate as justification for self-assessment performed by peers. Therefore, adding a knowledge base of the actions/practices carried out by the course.